THE INFLUENCE OF THE PROTECTED AREAS ON THE PRESENT DISTRIBUTION OF THE HIMALAYAN BROWN BEAR (URSUS ARCTOS ISABELLINUS HORSFIELD, 1826) POPULATION IN THE TRANS-ILI ALATAU, SOUTH-EAST KAZAKHSTAN (Experimental biology, 2024)
The aim of this study is to assess the current distribution of the Tian Shan brown bear (Ursus arctos isabellinus Horsfield, 1826) in two study areas: the Almaty State Nature Reserve (ANR) and in the adjacent territories of the Ile-Alatau State National Nature Park (IANP) between 2005 and 2018. Both areas are characterized by different degrees of anthropogenic transformation and conservation measures.Data collection was carried out using two techniques: ground survey (GS) in 2005-2013 and a camera trapping survey (CT) in 2013-2018.The comparison of the data obtained by the two methods, GS and CT, showed that the CT data is more extensive as it confirms and supplements the data collected with traditional GS methods.The Kilometric Abundance Index (KAI) was 0.56 (±0.33) individuals per km in the ANR and 0.41 (±0.23) individuals per km in the IANP. Using CT, the average occurrence index was 4.4 registrations per 100 trap days in ANR, while 2.9 registrations per 100 trap days in IANP.We observed the bears to have different daily activity patterns in the two study areas, with the bears appearing to be active throughout the day in ANR, and mainly active during the night and early morning in IANP.This study outlines the role of the territory of the ANR as the nucleus for the settlement of brown bear individuals in the Trans-Ili Alatau Mountain range, due to the abundance of the species remaining high for 40 years. The high observation rate (photos and direct observations) suggest that the bear population has a healthy conservation status. The territory of the IANP can serve as a buffer zone where individual groups of bears can function successfully, provided that they are afforded good protection and that low anthropogenic impact is maintained. On the other hand, the presence of bears in the IANP was mainly observed in sectors with low level of human activity.
Keywords: Tian Shan (Himalayan) brown bear, Trans-Ili Alatau Mountain range, protected areas